Teoria dos grafos aplicada à análise musical - Eduardo de Markus Athayde (2020)
This dissertation sought in Graph Theory a way to further improve the field of musical analylis. The research begins with the computational modeling of Gyorgy Ligeti’s Musica ricercata VII theme and ostinato. Differences regarding style between melodies generated by the model and Ligeti’s original theme prompted a reevaluation of the modeling proceedings. For this matter, Graph Theory is used as a tool for musical data visualization, assisting in the model’s problem identification. Beyond the effectiveness in solving the above objective, Graph Theory was used as a tool for musical analysis.